A validity and reliability of instrument to evaluate the principal technology leadership: a pilot study - Nawawi, Wirda; Alias, Bity Salwana; Wan Isa, Wan Mohd Khairul (Institute of Advanced Engineering and Science, 2024)
Rapid development of the digital environment nowadays requires a line of educational leadership, especially leaders in schools who are competent in technological leadership. Therefore, this study aims to verify the technology leadership instrument among school principals. Accordingly, a pilot study has been carried out to determine and confirm the level of instruments that have been built to identify the principal’s technology leadership practices. This pilot study was conducted on 196 samples consisting of secondary school teachers. This study examines the principal’s role as a technology leader involves five specific standards which includes the dimension of supporting digital citizenship, visionary planner, empowering leader, system designer and connected learner. This study has been conducted through three levels of validity namely face validity, content validity, and construct validity. Content validation index (CVI) is used to determine reliability between experts achieved. The construct validity is measured by exploratory factor analysis (EFA) and confirmatory factor analysis (CFA). The reliability of the instrument is measured by Cronbach alpha value. The finding of this pilot study shows that the instrument is valid and reliable. Finally, out of 50 items, 49 items are retained.